Status and development of administrative responsibility - Добрянська, Наталія Валеріївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2015)
The question of development of administrative responsibility is considered in the article, investigational subjects of administrative responsibility, foundation of administrative responsibility. The features of administrative responsibility are considered, maintenance of concept of administrative responsibility is exposed in accordance with a legislation.